The evolution of modern demand theory: a collection of essays - Ekelund, Robert B.; Furubotn, Eirik Grundtvig; Gramm, Phil (Lexington, Mass.: Lexington Books, 1972)
The purpose of this collection of essays is to bring together, under one cover, a good sample of the diverse literature dealing with demand theory.
Bibliography: p. 95-106.
rpm 01/08/2017
Loans
Keywords: Supply and demand; Economics